2022
DOI: 10.1021/acsanm.1c04085
|View full text |Cite
|
Sign up to set email alerts
|

CoNi Layered Double Hydroxide Nanosheets Vertically Grown on Electrodeposited Dendritic Copper Substrates for Supercapacitor Applications

Abstract: Layered double hydroxides (LDHs) have attracted numerous interests in developing high-performance electrochemical supercapacitors (SCs). However, the anchored conductive substrates are critical in the high-dense growth of LDH with favorable crystal orientations for maximizing performances, in which the conventional amorphous carbon-based materials and microporous nickel foams cannot be fitted. Herein, we utilize the electrodeposited 3D dendritic copper as the conductive substrate for the vertical growth of CoN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The electrochemical performance of the synthesized sample was measured on a CHI 660E (Chenhua) electrochemical workstation, including cyclic voltammetry (CV), constant current charge–discharge (GCD) and electrochemical impedance spectroscopy (EIS). The formulas for calculating the areal capacitance ( C a and C h ) are as follows: 34 where C a (F cm −2 ) and C h (mA h cm −2 ) are the areal capacitance, I (A) is the discharge current, t (s) is the discharge time, S (cm 2 ) is the geometrical area of the electrode and Δ V (V) is the potential window. 35…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical performance of the synthesized sample was measured on a CHI 660E (Chenhua) electrochemical workstation, including cyclic voltammetry (CV), constant current charge–discharge (GCD) and electrochemical impedance spectroscopy (EIS). The formulas for calculating the areal capacitance ( C a and C h ) are as follows: 34 where C a (F cm −2 ) and C h (mA h cm −2 ) are the areal capacitance, I (A) is the discharge current, t (s) is the discharge time, S (cm 2 ) is the geometrical area of the electrode and Δ V (V) is the potential window. 35…”
Section: Methodsmentioning
confidence: 99%
“…LDH nanosheets are known as anionic clays, which are composed of positively charged metal layers, interlayer anions, and H 2 O molecules, which are currently one of the most thoroughly researched layered materials. , The general formula for LDHs is expressed as [M 2+ 1– x M 3+ x (OH) 2 x + (A n – ) x / n ] x + ·mH 2 O, where M 2+ (Mg 2+ , Ni 2+ , Zn 2+ , etc.) is the metal divalent, M 3+ (Al 3+ , Mn 3+ , Co 3+ , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In this work, our focus was to study the electrodeposition of CoNi, which is an important electrocatalytic material for energy reactions. Butynediol has been used to control the roughness and texture of the CoNi alloy . Our previous study showed that the flux of butynediol and protons affects the electrochemical oscillation that involved adsorbed hydrogen and cobalt hydroxide during the electrodeposition of cobalt under quiescent conditions .…”
Section: Introductionmentioning
confidence: 99%